Development of Early Flood Detection & Warning System - Wan Mohd Zulkifli, Wan Siti Zulaikha binti; Lam , Hong Yin (Progress in Engineering Application and Technology, 2023)
Flooding is a major hazard in Malaysia due to the country's proximity to the equator, which often leads to property damage and loss of life. In order to mitigate these effects, early detection and warning systems are necessary to alert the local community about evacuation plans and property protection. This project focuses on developing a prototype of such a system that uses Internet of Things technology, ultrasonic sensors, and water level sensors controlled by an Arduino microcontroller to detect flood water depths at different locations in real time and send warning messages to users via instant mobile short message services. The prototype system also has a web-based graphic interface that allows users to access real-time information about local water levels. The system records data with a resolution of one second but displays it every minute, and takes into account local river water level thresholds from the Ministry of Energy and Natural Resources to accurately reflect the specific location. The system's performance was tested at three locations with various water level heights and was found to be effective. It is hoped that this prototype system can serve as a preventive measure against flood disasters in flood-prone areas and can be expanded into larger-scale systems that provide real-time flooding information and warnings to the local community.